NURSING STUDENTS KNOWLEDGE AND ATTITUDE TOWARDS VITAL SIGN MONITORING DURING CLINICAL PRACTICE - HANIF, M; SADDIQUE, H; TASNEEM, S (Biological and Clinical Sciences Research Journal, 2024)
Vital sign monitoring is a fundamental nursing skill critical for early identification of clinical deterioration and effective patient management. However, gaps in knowledge and inconsistent practices among nursing students can compromise patient safety. This study aimed to assess the knowledge, attitudes, and practices of nursing students regarding vital sign monitoring in a tertiary care hospital in Lahore, Pakistan. Methods: A descriptive cross-sectional study was conducted among 130 nursing students enrolled in Bachelor of Science in Nursing (BSN) and Post Registered Nurse (Post RN) programs. Data were collected using a structured, prevalidated questionnaire covering demographic details, knowledge, and attitudes related to vital sign monitoring. Statistical analysis was performed using SPSS version 26, with descriptive and inferential statistics employed to summarize findings and identify associations. Results: The study revealed moderate knowledge levels among participants, with 58.6% able to relate vital signs to pathophysiology. However, 53.4% reported limited knowledge in interpreting vital sign changes. Attitudes were generally positive, with 45.1% relying on standard respiratory rate ranges when SpO2 levels were normal. Practical gaps were noted, including reliance on technology rather than manual monitoring. Education and experience significantly influenced knowledge and attitudes (p < 0.05).Conclusion: While nursing students demonstrated moderate knowledge and positive attitudes, critical gaps in practices and specific knowledge areas were identified. Enhanced training programs, simulation-based learning, and regular competency assessments are essential to improve vital sign monitoring skills among nursing students, ensuring better patient safety outcomes.